Menangkal Radikalisme Agama Berdasarkan Reinterpretasi Amanat Agung Injil Matius Dalam Konteks Poskolonial - Alvary Exan Rerung (Institut Agama Kristen Negeri Toraja, 2022)
For the Indonesian nation, which is a nation with a pluralistic society, religions have an important role to play in creating a nation with a peaceful and harmonious society in order to create national unity and progress. But it is a fact that often conflicts and divisions that occur are the result of religion itself, especially if the religious ideology is contrary to the values of Pancasila which uphold tolerance. Seeing this reality, an attitude is needed to see how the teachings of each religion are for its adherents. Specifically for Christianity, by using qualitative research methods and literature studies, this paper intends to reinterpret the great message which is currently attached to interpretation, namely the command to Chirstianize due to the influence of colonialism. Because the meaning of Christianity is no longer relevant for Indonesia and has even become a sensitive meaning for adherents of other religions. That is why, this paper wants to offer a post-colonial spirit to be able to reinterpret the wrong interpretation of the Great Commission, so that the interpretation is more relevant to the context in Indonesia. So that it can help the government in efforts to counter religious radicalism. Abstrak: Bagi bangsa Indonesia yang merupakan bangsa dengan masyarakat majemuk, agama memiliki peran penting untuk menciptakan bangsa dengan kondisi masyarakat yang damai dan harmonis agar bisa tercipta keutuhan serta kemajuan bangsa. Tetapi menjadi suatu kenyataan bahwa seringkali konflik dan perpecahan yang terjadi adalah hasil dari agama itu sendiri, apalagi jika ideologi agama itu bertentangan dengan nilai-nilai Pancasila yang menjunjung tinggi toleransi. Melihat realita itu, maka diperlukan sikap untuk melihat bagaimana ajaran masing-masing agama bagi para pemeluknya. Secara khusus bagi agama Kristen, dengan menggunakan metode penelitian kualitatif deskriptif dan studi pustaka, tulisan ini hendak melakukan reinterpretasi terhadap amanat agung yang dewasa ini sudah melekat dengan interpretasi, yaitu perintah untuk mengkristenkan akibat pengaruh kolonialisme. Sebab makna kristenisasi tidaklah lagi relevan bagi Indonesia dan malah menjadi makna yang sensitif bagi penganut agama lainnya. Itulah sebabnya, tulisan ini hendak menawarkan semangat poskolonial untuk bisa melakukan reinterpretasi terhadap interpretasi keliru dari amanat agung, agar interpretasinyanya lebih relevan dengan konteks yang ada di Indonesia. Karena hal tersebut dapat membantu pemerintah dalam upaya menangkal radikalisme agama.